2002
DOI: 10.1177/000992280204100605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Temple Temperatures with Rectal Temperatures in Children Under Two Years of Age

Abstract: We assessed the agreement between rectal and noninvasive temporal artery temperature measurements in infants and children. We also evaluated the temple thermometer as a screening tool for rectal fever in this age group. Finally, we compared the performance of parents with that of nurses in using the temple thermometer. The 95% limits of agreement between the difference in rectal and average temple temperature were -1.03 and +1.52 degrees C. Mean temple temperatures obtained by parents and by nurses were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
44
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
5
44
0
1
Order By: Relevance
“…If accurate, TA thermometers offer all the advantages of tympanic thermometry without the problem of the operator needing to aim the instrument blindly at the tympanic membrane. Readings obtained by parents closely match those obtained by nurses (26). The well-conducted study by Al-Mukhaizeem et al (pages 461-465) demonstrated that TA readings were as accurate as rectal readings, using esophageal readings as the reference standard.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…If accurate, TA thermometers offer all the advantages of tympanic thermometry without the problem of the operator needing to aim the instrument blindly at the tympanic membrane. Readings obtained by parents closely match those obtained by nurses (26). The well-conducted study by Al-Mukhaizeem et al (pages 461-465) demonstrated that TA readings were as accurate as rectal readings, using esophageal readings as the reference standard.…”
supporting
confidence: 61%
“…The well-conducted study by Al-Mukhaizeem et al (pages 461-465) demonstrated that TA readings were as accurate as rectal readings, using esophageal readings as the reference standard. However, previous studies showed TA readings to have poor sensitivity at detecting fever, using rectal (26,27) or PA (28) readings as the reference standard. One possible explanation is that only two of the 80 children in the Al-Mukhaizeem et al study were febrile, and possibly, TA thermometers perform best in the normothermic range.…”
mentioning
confidence: 99%
“…이마체 온은 직장체온이나 고막체온보다 더 정확하고 (Greenes & Fleisher, 2001), 아동의 발열상태를 잘 감별해 내며 (Siberry, Diener -West, Schappell, & Karron, 2002), 구강체온보다 더 정확할 뿐 아니라 폐동 맥은 물론 식도의 심부체온에 필적한다는 보고가 있다 (Carroll, Finn, Judge, Gill, & Sawyer, 2004). 그러나 이마체온은 안정시의 체온 은 잘 반영하지만 발열상태는 잘 감별해 내지 못한다는 상반된 연 구 결과도 보고되고 있다 (Kimberger, Cohen, Illievich, & Lenhardt, 2007;Kistemaker, Den Hartoq, & Daanen, 2006;Ronneberg, Roberts, McBean, & Center, 2008) (Kimberger et al, 2007;Kistemaker et al, 2006;Lawson et al, 2007;Ronnerberg, Roberts, McBean, & Center, 2008) Table 2).…”
unclassified
“…(Pediatr Crit Care Med 2005; 6:557-561) KEY WORDS: temperature; children; temporal artery thermometry membrane thermometers has been applied to develop a noninvasive temporal artery (TA) thermometer (18 -21). The rationale for using the temporal artery for temperature measurement stems from its site and unique physiologic characteristics (18,21). Measurement of temperature via skin areas perfused by the superficial TA provides an easily accessible area that does not require contact with mucous membranes.…”
mentioning
confidence: 99%